Simple carbon fiber graphitization device for in-situ measurement of small angle X-ray scattering (SAXS). Issue 1 (2nd January 2021) - Xiao, Peng; Li, Dongfeng; Gong, Yanjun; Zhang, Shujiao; Mo, Guang; Li, Zhihong
Abstract: A small and simple device for the in-situ small angle X-ray scattering (SAXS) measurement of carbon fibers graphitization by direct electrical heating was developed. The graphitization process of polyacrylonitrile-based T700 carbon fibers from 1450 °C to 2100 °C with this device was followed in-situ by synchrotron radiation SAXS. The results show that there are needle-shaped voids oriented preferentially along the fibers axis with a surface fractal structure during graphitization of carbon fibers. The change in the fractal dimension as a function of temperature includes a dip with a minimum value at approximately 1700 °C. This short contribution briefly describes the device and analyzes the obtained experimental results.